The Effect of Contextual-Based Discovery Learning Model on Improving Science Abilities of Children Aged 5-6 Years - Khusnul Aini Syam; Parwoto Parwoto; Sitti Nurhidayah Ilyas (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This study aims to determine the effect of a context-based discovery learning model through floating and sinking experimental activities on the science abilities of children aged 5-6 years at Raudhatul Jannah Kindergarten. This study employs a quantitative approach with a quasi-experimental research type using a pretest-posttest control group design. The research sample consisted of 20 children, comprising 10 children in the experimental group and 10 children in the control group, selected using a purposive sampling technique. Data collection techniques were carried out through observation, tests, and documentation. Data analysis used descriptive statistics as well as nonparametric tests, namely the Wilcoxon Signed Rank Test and Mann-Whitney U Test, with the assistance of SPSS. The results showed that the science abilities of children in the experimental group experienced a more optimal improvement compared to the control group. The results of the Wilcoxon Signed Rank Test in the experimental group showed an Asymp. Sig. (2-tailed) value of 0.004 < 0.05, indicating a significant effect of the application of the context-based discovery learning model on the science abilities of children aged 5-6 years. Improved science skills were observed in children's ability to observe, predict, classify, and draw conclusions from simple experiments through floating and sinking experimental activities.